The Role of Agriculture in Development - Gollin, Douglas; Parente, Stephen; Rogerson, Richard (American Economic Review, 2002)
A longstanding question in economics is why some countries are so much richer than others. Today, for example, income per capita in the world's richest countries is roughly thirty-five times greater than it is in the world's poorest countries. Recent work argues that the proximate cause of the disparity is that today's poor countries began the process of industrialization much later and that this process is slow. In this paper we argue that a model of structural transformation provides a useful theory of both why industrialization occurs at different dates, and why it proceeds slowly. A key implication of this model is that growth in agricultural productivity is central to development, a message that also appears prominently in the traditional development literature.